Effect of sodium silicate on the dimensional stability and mechanical behaviour of non-woven flax reinforced acrylic based polyester composites / Mohd Fadli Ahmad Rasyid... [et al.] - Ahmad Rasyid, Mohd Fadli; Salim, Muhamad Saifuddin; Zakaria, Muhammad Razlan; Mad Akil, Hazizan; Mohd Ishak, Zainal Arifin; Ahmad Thirmizir, Mohd Zharif (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
This paper investigated the effects of Sodium Silicate on the dimensional stability and mechanical behaviour of non-woven flax reinforced acrylic based polyester composites (NWFRAC) with 10, 20 and 30 wt% sodium silicate as filler which have been fabricated using the impregnation method. Water absorption tests were conducted by immersing specimens in a de-ionized water bath at 23 °C for different time durations. The tensile and flexural were investigated before and after water absorption. The percentage of moisture uptake increased as the increasing of sodium silicate content. The tensile and flexural properties of NWFRAC were found to decrease with increase in water uptake. The phase morphology of non-woven flax reinforced acrylic based polyester composites were investigated by using confocal laser microscope model Zeiss LFM 700 MATSEM. Higher sodium silicate content exhibits an irregular structure with many air gaps.